Partisipasi Masyarakat dalam Musyawarah Desa (Musdes) sebagai Instrumen Pencapaian Sustainable Development Goals (SDGS) Desa(Studi Kasus Desa Sinar Danau, Kecamatan Buana Pemaca, Kabupaten Ogan Komering Ulu Selatan) - Ikke Anggesti; Eva Susanti; Herni Ramayanti (Jurnal Ilmiah Multidisiplin Ilmu, 2026)
Community participation in Village Deliberation is a crucial element in realizing democratic, transparent, and inclusive village governance. Village Deliberation functions not only as a decision-making forum but also as a strategic instrument for achieving the Village Sustainable Development Goals (Village SDGs). This study aims to analyze the role of community participation in Village Deliberation as an instrument for achieving the Village SDGs through a case study in Sinar Danau Village, Buana Pemaca Subdistrict, Ogan Komering Ulu Selatan Regency. This research employed a qualitative approach with a case study design. Data were collected through observation, in-depth interviews with village government officials, the Village Consultative Body (Badan Permusyawaratan Desa/BPD), community leaders, and local residents, as well as documentation. The data were analyzed using the interactive model of Miles and Huberman, consisting of data reduction, data display, and conclusion drawing. The findings indicate that community participation plays a significant role in improving the quality of village development planning, budget transparency, and the implementation of sustainable development programs. Nevertheless, several challenges remain, including limited public participation, unequal representation of community groups, and the limited capacity of village officials in facilitating participatory development planning. Therefore, strengthening the capacity of both the community and village officials is essential to enhance the effectiveness of Village Deliberation as an instrument for achieving the Village SDGs.